Peran Akuntansi Pemerintahan Dalam Meningkatkan Transparansi Pengelolaan Keuangan Daerah - Sari, Wona Yuni; Maulina, Isra (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
Transparency of regional financial management is a key element in realizing good governance. Accurate, relevant, and accountable financial information is very important in government accounting. The role of government accounting in improving regional financial transparency is examined in this study. The results of the study indicate that the implementation of accrual-based Government Accounting Standards (SAP), the use of technology-based financial information systems, and strengthening human resource capacity are important factors in encouraging public information disclosure. However, a number of obstacles are still faced, such as limited technological infrastructure, low understanding of officials, and weak monitoring systems. This study emphasizes that cooperation between institutions, technology, and policies is very important to improve regional financial accountability and transparency.